Deregulation and privatization in Nigeria: the advantages and disadvantages so far (2013)
The economic principles of deregulation and privatization were first introduced in Nigeria in the 1980s through the policy of structural adjustment programme (SAP). Since then, government monopolies had disappeared in many industries and over 85 public enterprises (PES) in mining, education, health, agriculture, transportation and telecommunication were transferred, either fully or partially to private owners. The dangers of these principles, however, hardly ever occur to the average Nigerian until recently when the government declared a no-going-back decision to privatize the downstream sector of the petroleum industry. Today questions are being asked about the essence of privatization in Nigeria and it is the focus of this paper too to ask probing questions into the nature, practice and the context of deregulation and privatization in Nigeria. The inquiry centers on the benefits and the expected challenges that have come to characterize the ideas of the two concepts. However, from the content analysis of literature reviewed, the authors showed that the outcome of deregulation and privatization in Nigeria is mixed generally, having both positive and negative socio-economic consequences. Therefore, the paper concluded with recommendations to reform the reform through the involvement of labour unions, increased socio-economic stability and the establishment of more efficient regulatory agencies.